Ozone-primed neutrophils promote early steps of tumour cell metastasis to lungs by enhancing their NET production. Issue 8 (29th May 2019) - Rocks, Natacha; Vanwinge, Céline; Radermecker, Coraline; Blacher, Silvia; Gilles, Christine; Marée, Raphael; Gillard, Alison; Evrard, Brigitte; Pequeux, Christel; Marichal, Thomas; Noel, Agnes; Cataldo, Didier
Abstract : Background: Air pollution, including particulates and gazes such as ozone (O3 ), is detrimental for patient's health and has repeatedly been correlated to increased morbidity and mortality in industrialised countries. Although studies have described a link between ambient particulate matter and increased lung cancer morbidity, no direct relation has yet been established between O3 exposure and metastatic dissemination to lungs. Objectives: To outline the mechanisms through which pulmonary O3 exposure modulates metastasis kinetics in an experimental mouse model of O3 exposure. Methods: Metastatic responses to pulmonary O3 exposure were assessed using a reliable experimental mouse model of concomitant pulmonary O3 exposure and tumour cell injection. Roles of neutrophils in O3 -induced lung metastasis were highlighted using blocking anti-Ly6G antibodies; moreover, the implication of neutrophil extracellular traps (NETs) in metastatic processes was evaluated using MRP8cre-Pad4lox/lox mice or by treating mice with DNase I. Results: Pulmonary O3 exposure strongly facilitates the establishment of lung metastasis by (1) Inducing a pulmonary injury and neutrophilic inflammation, (2) Influencing very early steps of metastasis, (3) Priming neutrophils' phenotype to release NETs that favour tumour cell colonisation in lungs. The ability of O3 -primed neutrophils to enhance lung colonisation by tumour cells was proven after their adoptive transfer in Balb/c mice unexposed to O3 . Conclusions: Pulmonary neutrophils induced by O3 promote metastatic dissemination to lungs by producing NETs. These findings open new perspectives to improve treatment and prevention strategies in patients affected by metastatic diseases.